Consequences of culturally-driven ecological specialization: Killer whales and beyond. (7th November 2018) - Whitehead, Hal; Ford, John K.B.
Highlights: Culturally-driven ecological specialization increases fitness in the short term. Generalization is rarely adaptive. Culturally-driven ecological specialization increases group extirpation rates. Specialization tends to reduce population size and resource abundance. Culture can drive specialization much faster than natural selection. Abstract: Culturally-transmitted ecological specialization occurs in killer whales, as well as other species. We hypothesize that some of the remarkable demographic and ecological attributes of killer whales result from this process. We formalize and model (using agent-based stochastic models parametrized using killer whale life history) the cultural evolution of specialization by social groups, in which a narrowing of niche breadth is spread and maintained in a group through social learning. We compare the demographic and ecological results of cultural specialization to those of a similar model of specialization through natural selection. We found that specialization, through either the cultural or natural selection routes, is adaptive in the short term with specialization often increasing fitness. Generalization, in contrast, is rarely adaptive. The cultural evolution of specialization can lead to increased rates of group extirpation. Specialization has little effect on group size but tends to reduce population size and resource abundance. While the two specialization processes produce similar results, cultural specialization can be very much faster. The results are generally consistent with what we know of the formation and maintenance of specialist ecotypes in killer whales, and have implications for the persistence, nature and ecological effects of these apex predators.